Cuvântul Editorului - Romeo Teodor CRISTINA (Medicamentul Veterinar)
The time elapsed since the establishment of the Medicamentul Veterinar / Veterinary Drug Journal has so far, revealed that the efforts made by the editorial staff have been inspired, as a result of his passion and work. This is why the Journal will continue its journalistic activity in the field of veterinary and zoo-technical sciences. The year 2018 is assessed with the main achievements and failures of the Veterinary Medicine / Veterinary Drug Magazine as well as the guidelines for the next period.